2022
DOI: 10.3390/vaccines10071034
|View full text |Cite
|
Sign up to set email alerts
|

GMMA as an Alternative Carrier for a Glycoconjugate Vaccine against Group A Streptococcus

Abstract: Group A Streptococcus (GAS) causes about 500,000 annual deaths globally, and no vaccines are currently available. The Group A Carbohydrate (GAC), conserved across all GAS serotypes, conjugated to an appropriate carrier protein, represents a promising vaccine candidate. Here, we explored the possibility to use Generalized Modules for Membrane Antigens (GMMA) as an alternative carrier system for GAC, exploiting their intrinsic adjuvant properties. Immunogenicity of GAC-GMMA conjugate was evaluated in different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…GAC was purified, as previously described [ 35 ], from the GAS51∆M1 strain, an M protein mutant of HRO-K-51, which was kindly provided by the University of Rostock. Vi was obtained from Citrobacter NVGH 328 isolate, according to the procedure previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…GAC was purified, as previously described [ 35 ], from the GAS51∆M1 strain, an M protein mutant of HRO-K-51, which was kindly provided by the University of Rostock. Vi was obtained from Citrobacter NVGH 328 isolate, according to the procedure previously described [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…The group of Micoli et al has reported extensively on their GMMA carriers originating from different pathogens and conjugating various polysaccharide and protein antigens [ 53 , 64 ]. Palmieri et al have investigated conjugates using GMMAs originating from S. enterica and conjugating Group A Streptococcus cell wall oligosaccharide [ 65 ], whereas Scaria et al describe the application of OMV, a membrane vesicle derived from N. meningitidis as the carrier for a malaria transmission-blocking antigen.…”
Section: Conjugate Vaccine Carriersmentioning
confidence: 99%
“…Those factors should be considered when using this technology in vaccine design to fully exploit this technology as a platform for a multicomponent vaccine. Recently, for group A Streptococcu s, GMMA was successfully used as a carrier system for the glycoconjugate vaccine [90]. This technology resulted in a higher immune response in mice treated and immunised with GAC‐GMMA conjugate.…”
Section: Emerging Technology In Vaccine Designmentioning
confidence: 99%